2016
DOI: 10.1530/eje-16-0202
|View full text |Cite
|
Sign up to set email alerts
|

ENDOCRINE TUMOURS: Advances in the molecular pathogenesis of thyroid cancer: lessons from the cancer genome

Abstract: Thyroid cancer is the most common endocrine malignancy giving rise to one of the most indolent solid cancers, but also one of the most lethal. In recent years, systematic studies of the cancer genome, most importantly those derived from The Cancer Genome Altas (TCGA), have catalogued aberrations in the DNA, chromatin, and RNA of the genomes of thousands of tumors relative to matched normal cellular genomes and have analyzed their epigenetic and protein consequences. Cancer genomics is therefore providing new i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 70 publications
2
33
0
7
Order By: Relevance
“…2,3 The carcinogenesis and tumor progression of thyroid cancer result from varieties of factors, including variation of gene expression and changing activity in signaling pathways. 4,5 Dysregulation of miRNAs has been documented to be implicated in a number of cancers, 8,9 including thyroid cancer. 10 Therefore, the exploration on miRNAs in thyroid cancer is helpful for the identification of potential biological markers for thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 The carcinogenesis and tumor progression of thyroid cancer result from varieties of factors, including variation of gene expression and changing activity in signaling pathways. 4,5 Dysregulation of miRNAs has been documented to be implicated in a number of cancers, 8,9 including thyroid cancer. 10 Therefore, the exploration on miRNAs in thyroid cancer is helpful for the identification of potential biological markers for thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1 Past decades have witnessed a rising death rate due to the occurrence of thyroid cancer. 4,5 Therefore, effective therapeutic biological targets are in imminent need to be identified in thyroid cancer. 4,5 Therefore, effective therapeutic biological targets are in imminent need to be identified in thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A recent pan-cancer analysis on whole exome sequencing revealed that the mutation frequency in PTC was one of the lowest (approximately 1 change/Mb across the entire exome) among solid tumors (Lawrence et al 2013) (Fig. 4), while the mutation frequency in ATC was at the opposite extreme and was closer to that in melanoma and lung cancer, exceeding 100 changes/Mb (Kunstman et al 2015, Riesco-Eizaguirre & Santisteban 2016. As mutations are largely caused by errors in DNA replication (Tomasetti et al 2017), some researchers propose that the cell division rate also participates in shaping the cancer DNA methylation landscape (Yang et al 2016b).…”
Section: Dna Methylation Changes In Thyroid Cancer: Drivers Of Diseasmentioning
confidence: 92%
“…Page 2 of 14 Liu et al J Transl Med (2020) 18:170 cancer [2]. In recent years, researchers believe that the major carcinogenic event of PTC is the activation of mitogen-activated protein kinase (MAPK) [3]. However, the mechanisms underlying the pathogenesis of PTC have not yet been elucidated.…”
mentioning
confidence: 99%